Microphytoplanktonic assemblage in a region with upwelling events on the north coast of Bahia, Brazil - Affe, Helen Michelle de Jesus; Ferreira dos Santos, Márcio; de Castro Nunes, José Marcos; Oliveira dos Santos, Francisco Kelmo; de Souza, Christiane Sampaio; Mafalda Júnior, Paulo de Oliveira (Revista de Biología Marina y Oceanografía, 2024)
This study aimed to characterize seasonal changes in microphytoplankton composition and abundance on Bahia continental shelf, a region with upwelling events. Semi-annual sampling was conducted during summer and winter from 2017 to 2021 at nine points. Microphytoplankton was sampled using a conical plankton net through horizontal subsurface drags, using a flowmeter coupled to the net, to measure the total volume of filtered water. Temperature and salinity were measured in situ, presenting typical values of tropical waters. In addition, dissolved inorganic nutrient concentration corroborated a tropical marine oligotrophic pattern. A total of 151 taxa were identified in the region, with the phyla Heterokontophyta and Dinoflagellata being the most representative, as is typically recorded in tropical coastal regions. The density ranged from 6.08 × 104 to 3.38 × 108 cells L-1, with higher average values in summer. Although cyanobacteria accounted for only 3.2% of species richness in the region, due to summer blooms of Trichodesmium erythraeum (2018, 2019, and 2021), it was the most abundant group throughout the study. It was observed that upwelling events do not seem to establish favorable conditions for marked seasonal changes in microphytoplankton composition and abundance. Trichodesmium erythraeum blooms are closely related to physiology and ecological capacity of this species. Except for bloom periods, the study area presented a high species richness and diversity throughout the analyzed time series.